2013
DOI: 10.15623/ijret.2013.0208060
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Adoption of Building Information Modelling (Bim) in the Malaysian Construction Industry: A Qualitative Approach

Abstract: The construction industry believes that Building Information Modelling (BIM) is a platform that has the potential to promote

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Previous studies (Zahrizan et al 2013;McAuley et al 2017) argued that the successful application of BIM (CSF Grouping 1) would probably influence the advantages and government support of BIM implementation (CSF Grouping 3). In order to test this argument, this study changed the path direction of hypothesis 3 and deleted CSF Grouping 2 in the SEM model, otherwise the three influence paths would become a loop of the same direction which is meaningless in mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Zahrizan et al 2013;McAuley et al 2017) argued that the successful application of BIM (CSF Grouping 1) would probably influence the advantages and government support of BIM implementation (CSF Grouping 3). In order to test this argument, this study changed the path direction of hypothesis 3 and deleted CSF Grouping 2 in the SEM model, otherwise the three influence paths would become a loop of the same direction which is meaningless in mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge and awareness (Bin Zakaria et al, 2013;Gerrard et al, 2010;Khosrowshahi and Arayici, 2012) Lack of support from policy makers (Abubakar et al, 2014;Bin Zakaria et al, 2013) Unavailability of standards and guidelines (Azhar, Khalfan and Maqsood, 2015;Bin Zakaria et al, 2013;Chan, 2014;Manderson, Jefferies and Brewer, 2015) Initial costs (Abubakar et al, 2014;Azhar, Khalfan and Maqsood, 2015;Forsythe, 2014;Gerrard et al, 2010;Khosrowshahi and Arayici, 2012;Rodgers et al, 2015) Training and learning issues (Abubakar et al, 2014;Azhar, Khalfan and Maqsood, 2015;Chan, 2014) Incompatibility and interoperability problems (Azhar, Khalfan and Maqsood, 2015;Manderson, Jefferies and Brewer, 2015;Rodgers et al, 2015) Lack of demand (Azhar, Khalfan and Maqsood, 2015;Chan, 2014;Khosrowshahi and Arayici, 2012;Poirier, Staub-French and Forgues, 2015a;Rodgers et al, 2015) Lack of skilled personnel (Azhar, Khalfan and Maqsood, 2015;Chan, 2014;Gerrard et al, 2010;Rodgers et al, 2015) Resistance to change (Abubakar et al, 2014;Azhar, Khalfan and Maqsood, 2015;Forsythe, 2014;Gerrard et al, 2010;Khosrowshahi and Arayici, 2012;Poirier, Staub-French and Forgues,...…”
Section: Barriers Referencementioning
confidence: 99%
“…Previous studies have reported that various factors influence the successful adoption and implementation of BIM. For instance, Arayici et al (2009) and Zahrizan et al (2013) identified the following critical enablers for the successful adoption of BIM in contractor and consulting firms respectively: educating and training staff about BIM hardware, software and process/workflow changes; having efficient information management systems to facilitate effective collaboration and communication; and creating an organisational culture that embraces change. Ahuja et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2019). A few studies (e.g., Arayici et al , 2009; Zahrizan et al , 2013) pay attention to explaining how specific factors impact BIM adoption. Such contributions are relevant and welcome additions to the literature.…”
Section: Introductionmentioning
confidence: 99%